(untitled) (Bangladesh Journal of Agricultural Research, 2022)
The study was conducted in three malta growing districts namely Khagrachori, Pirojpur and Chapai Nawabganj during January-March 2018. An attempt was made to assess the adoption status of BARI Malta-1 (sweet orange), its farm level profitability, problems and the impacts of malta cultivation on the livelihood of farmers. A total of 180 farmers, 60 farmers from each district were randomly selected for this study. The study revealed that 91% farmers adopted BARI Malta-1 in their gardens. Higher yield, profitability, sweetness, and less insect-pests infestations were the major reasons for choosing BARI Malta-1 at farm level. Farmers did not follow the recommended doses of manures and fertilizers due to lack of adequate knowledge on recommended doses. The establishment cost of a malta garden was Tk. 7,02,650 per hectare. The highest yield (19.6 t/ha) and gross return (Tk. 15,68,000/ha) were obtained from 5th to 10th year gardens. The lowest return (Tk. 8,28,160/ha) was reported in the 3rd year garden. Scarcity of saplings, un-attractive colour, and lack of technical know-how were the major problems to BARI Malta-1 cultivation. The study suggested availability of saplings, hands-on training to the farmers, and affordable price of different input for higher adoption of this variety. Bangladesh J. Agril. Res. 45(4): 473-491, December 2020